Mycorrhizal hyphae as ecological niche for highly specialized hypersymbionts – or just soil free-riders? - Jansa, Jan; Bukovská, Petra; Gryndler, Milan (Frontiers in Plant Science, 2013)
Mycorrhizal fungi interconnect two different kinds of environments, namely the plant roots with the surrounding soil. This widespread coexistence of plants and fungi has important consequences for plant mineral nutrition, water acquisition, carbon allocation, tolerance to abiotic and biotic stresses and interplant competition. Yet some current research indicates a number of important roles to be played by hyphae-associated microbes, in addition to the hyphae themselves, in foraging for and acquisition of soil resources and in transformation of organic carbon in the soil-plant systems. We critically review the available scientific evidence for the theory that the surface of mycorrhizal hyphae in soil is colonized by highly specialized microbial communities, and that these fulfill important functions in the ecology of mycorrhizal fungal hyphae such as accessing recalcitrant forms of mineral nutrients, and production of signaling and other compounds in the vicinity of the hyphae. The validity of another hypothesis will then be addressed, namely that the specific associative microbes are rewarded with exclusive access to fungal carbon, which would qualify them as hypersymbionts (i.e. symbionts of symbiotic mycorrhizal fungi). Thereafter, we ask whether recruitment of functionally different microbial assemblages by the hyphae is required under different soil conditions (questioning what evidence is available for such an effect), and we identify knowledge gaps requiring further attention.